Crown land in Australia - Babie, P (2001)
Property theory has long explored the meaning and content of private property. Similarly, one finds no shortage of analysis of common or communitarian property. In the theoretical literature, however, one finds very little writing about public property, a third, very significant, type of property. This lack of attention is not due to a lack of examples; on the contrary, examples abound. This thesis offers a theoretical analysis of one such example: Crown land in Australia. Crown land is a largely forgotten and therefore under-analysed aspect of Australian real property law. This lack of analysis has produced significant confusion in recent judicial developments concerning Australian common law native title. In order to alleviate the potential for confusion, this thesis fills a long-standing gap in the literature of Australian real property law. In order to fill this gap and to provide a much-needed analytical account, it is necessary to make use of working definitions of private, public and communitarian property. This thesis provides each. First, using JW Hams' Property and Justice, it constructs a working definition of private property. From that, by way of contrast, a working definition of public property is offered. Finally, by way of contrast to both private and public property, a working definition of communitarian property is also developed. Armed with working definitions of private, public and communitarian property, the thesis provides an analytical account of Crown land in Australia. It describes Crown land as the quasi-ownership use-privileges and control-powers which the Crown, by virtue of its prerogative power over land, enjoys in Australian land. The Crown enjoys differently packaged bundles of such privileges and powers over many different sorts of land, such as those which have never been allocated for any use, specific natural resources such as minerals or petroleum, those over which Australia's Aboriginal peoples enjoy native title, and even those over which private persons hold freehold estates or statutory leases. All such lands, due to the Crown's quasi-ownership privileges and powers therein, can be called Crown land, which embraces a continuum of locations, each defined by a unique package of such privileges and powers over the relevant type of land. The thesis calls this the Crown land continuum, which, in its totality, is a working example of public property.